2020
DOI: 10.1002/jac5.1224
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacist and family medicine clinic provision of chronic care management services for Medicare beneficiaries with uncontrolled hypertension

Abstract: Introduction: Pharmacist-physician collaboration has shown positive results in improving patient outcomes. Chronic care management (CCM) is a reimbursable service for Medicare beneficiaries in the community setting which includes comprehensive care management and other activities. The pharmacist contribution to CCM services and their associated impact on patient health outcomes has not been fully explored.Objectives: The objectives of this study were to: (a) implement a collaborative CCM service between a comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Medication adherence based on the medication possession ratio was significantly higher among the CMM group (CMM = 0.811 vs. usual care = 0.659, p < 0.005), and the CMM group subjects were more likely to switch therapy when indicated (24.2% vs. 5.4%, p = 0.001) 28 . A prospective single group prestudy and poststudy of hybrid CMM found improvement in systolic blood pressure (133 mmHg vs 140 mmHg, p = 0.006), but no change in diastolic blood pressure at 9 months 30 . Another single‐center prepilot and postpilot study of CMM via telehealth on a patient‐aligned care team noted a 2% reduction from baseline A1c at 6 months ( p = 0.0002; Table 4).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Medication adherence based on the medication possession ratio was significantly higher among the CMM group (CMM = 0.811 vs. usual care = 0.659, p < 0.005), and the CMM group subjects were more likely to switch therapy when indicated (24.2% vs. 5.4%, p = 0.001) 28 . A prospective single group prestudy and poststudy of hybrid CMM found improvement in systolic blood pressure (133 mmHg vs 140 mmHg, p = 0.006), but no change in diastolic blood pressure at 9 months 30 . Another single‐center prepilot and postpilot study of CMM via telehealth on a patient‐aligned care team noted a 2% reduction from baseline A1c at 6 months ( p = 0.0002; Table 4).…”
Section: Resultsmentioning
confidence: 96%
“…All studies included a pharmacist and a provider on their team conducting the interventions 23‐33 . The number of interprofessional team members delivering CMM varied from two to five members.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations